(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
The use of fluorescence as an analytical signal makes it possible to reduce the limits of detection of analytes. The study of spectral properties of luminophores is important for the development of new methods for analyzing various objects. The use of micellar systems enables to increase quantum yields by 2–10 times and fluorescence intensity by 3–80 times and reduce the limits of detecting analytes by 1–2 orders of magnitude. Organized media based on surfactants influence on the fluorescence of luminescent indicators and their complex compounds due to changes in their microspheric solution of their photophysical characteristics, aggregate state and microprobe nature. Cationic surfactants occupy a special place among cytotoxicants. Low levels of maximum permissible concentrations of cationic surfactants require the use of sensitive analytical methods that combine simplicity and availability with reliability and expressiveness. Known chemical and microbiological methods for the determination of cationic surface-active antiseptics, disinfectants and preservatives characterize by complexity and labor intensity and are not suitable for the operational control of their concentration in places of local use. Therefore, the purpose of the work was to study the influence of various types of surfactants on the fluorescence properties of fluorescein to develop a method for determining the content of ethonium. The influence of surface-active substances of different types on the fluorescence properties of fluorescein was investigate. The anionic surfactant almost does not effect on the intensity of the dye signal. Nonionic surfactant leads to a gradual decrease in the fluorescence intensity of fluorescein. The most visible influence was observe with adding into the solution cationic surface-active substances. There is harsh intensity decrease of the dye fluorescence with subsequent exit to the "plateau" in the system of fluorescein-cetylpyridinium chloride. The cationic surfactant ethonium works the same. Received results will laid in the basis of the method development of ethonium determination in the medical drugs.